Shuar Cosmovision in the Teaching and Learning Process in Palora Country - Quezada-Sarmiento, Pablo Alejandro; Xavier Andrés Barnuevo-Solís; Julio Cesar Amaguaya-Mendoza; Patricia Marisol Chango-Cañaveral; Eduardo Bladimir Aguirre-Maldonado; Angela Lucia Tuquerres-Chicaiza (My University, 2025)
This research explores the importance of ancestral knowledge, such as myths, which are transmitted orally in different families in cultural communities. However, this knowledge combined with popular knowledge can also be applied to education. Therefore, the objective of this work was to design a methodological strategy for ninth grade general education students through a variety of didactic resources in the fields of knowledge of language and national literature and knowledge of language and literature spanish. The work is based on the popular myth of the community “Shakaim/The God of Work”, in which morals and moral values are taught, incorporating popular knowledge, such as reading comprehension
Keywords: ancestors; ancestral knowledge; education; identity; Shuar worldview